2005
DOI: 10.1016/j.fm.2004.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Aeromonas hydrophila in fish and prawns from the seafood market of Coimbatore, South India

Abstract: Five hundred and thirty six samples of fishes and 278 prawn samples from the major fish market of Coimbatore, South India, were analysed for the prevalence of Aeromonas hydrophila over a period of 2 years (June 1997-May 1999). The prevalence level of A. hydrophila varied from 17.62% in prawns to 33.58% in fishes. More than 30% of the popular table fishes such as Sardinella longiceps, Rastrelliger kanagurta, Mugil cephalus and Caranx sexfasciatus were tested positive for this organism. Among the different speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 24 publications
2
38
0
2
Order By: Relevance
“…Also several investigations have shown that members of the genus Aeromonas are also widely distributed in various foods such as meat [9,10] , sea food [11][12][13][14] , and vegetable [15] . Thus, foods have been suggested as a vector in the dissemination of this pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Also several investigations have shown that members of the genus Aeromonas are also widely distributed in various foods such as meat [9,10] , sea food [11][12][13][14] , and vegetable [15] . Thus, foods have been suggested as a vector in the dissemination of this pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Aeromonads have been detected in dairy products (4 %), vegetables (26-41 %), meats and poultry (3-70 %), with the largest numbers recorded from shellfish (31 %) and fish (72 %) (Janda and Abbott 2010). Aeromonas hydrophila (DNA hybridization group, HG1), and Aeromonas veronii biovar sobria (HG8) (otherwise known as A. sobria) are the most common species belonging to this genus, often encountered in fish and fishery products (Rahman et al 2002;Vivekanandhan et al 2005). Aeromonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…In South India, description of new species [49]. The intraspecies the prevalence of Aeromonas in drinking water [34], diversity based on partial 16S rDNA sequence analysis finfish and prawn [35] and ornamental fishes [36,37] was observed in the variations in the biochemical emphasise the need for the surveillance of this reactions and antibiotic susceptibility of these strains. pathogen in the environmental reservoirs.…”
Section: Introductionmentioning
confidence: 99%